Navigating Dhule's Future: A BRTS Estimation Survey for Urban Mobility (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
India's rapid urbanization and economic growth have led to traffic congestion, pollution, and challenges in its cities. With a surge in private vehicles, urban planners are designing mass rapid transit systems to ensure safe and environmentally friendly mobility. Dhule, a smart city, is exploring measures to encourage public transportation, with Bus Rapid Transit Systems (BRTS) emerging as the most suitable mode for a mass transit system. This research project aims to analyze the existing transportation system in Dhule and the proposed BRTS system. A preference survey is being conducted to assess commuters' willingness to shift from their current mode of transport to the BRTS. Urban transport modeling, consisting of four steps, is used to predict travel patterns and evaluate pre- and post-BRTS implementation scenarios using a transport ecological footprint analysis.